Wind turbine blade

By coating the coating of polytramamine, the coating composition of the prefabricated of polytramamine, the fat rings, and the fatty cyanocyte prefabricated by the wind turbine's leaf edge, solve the problem of leaf wear and erosion. Realize higher rain resistance and durability.

CN119365509APending Publication Date: 2025-01-24JOTUN AS LTD

Patent Information

Application Number
CN202380046848.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2023-07-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The wear and erosion of wind turbine blades, especially in collisions with raindrops and particulate matter at high velocities at the tip of the blade, leads to insufficient durability.

Method used

A coating composition containing a polyaspartate, an alicyclic diamine aldimine, and an aliphatic polyisocyanate prepolymer is used to coat the leading edge of a wind turbine blade to improve its tensile properties and Durability.

Benefits of technology

The coating composition maintains performance after exposure to UV light, has good adhesion, has few film defects, and dries quickly, significantly improving the rain erosion resistance and durability of wind turbine blades.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185668730000041
    Figure BDA0005185668730000041
  • Figure BDA0005185668730000061
    Figure BDA0005185668730000061
  • Figure BDA0005185668730000062
    Figure BDA0005185668730000062
Patent Text Reader

Abstract

The invention relates to a wind turbine blade, preferably the leading edge of a wind turbine blade, coated with a coating composition comprising: (A) at least one polyaspartic substance selected from the group consisting of polyaspartic esters, polyether aspartic esters and mixtures thereof; and (B) at least one aliphatic polyisocyanate prepolymer curing agent; wherein component A further comprises an alicyclic diamine aldimine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a wind turbine blade, in particular the leading edge of a wind turbine blade, coated with a coating composition. In particular, the coating composition comprises at least one polyaspartic acid (polyaspartic acid, polyaspartic), at least one alicyclic diamine aldimine and at least one aliphatic polyisocyanate prepolymer. The present invention also relates to the use of the coating composition for a wind turbine blade. Background Art

[0002] A common challenge in the wind turbine industry is the wear and erosion of wind turbine blades, which is caused by the high speed at the blade tip combined with the collision of raindrops and particulate matter such as dust or sand. The whirling arm rain erosion test (RET) is often used to test durability.

[0003] Leading Edge Protection (LEP) is used to protect the highest speed (usually greater than 300km hr -1 ) of the blade portion (leading edge). A typical coating system for LEP includes at least one primer (e.g., polyurethane or polyaspartic acid) and a LEP coating.

[0004] It has been shown that in order to obtain high rain erosion resistance (i.e., longest durability), it is crucial to have large tensile stress and strain values. The tensile properties depend greatly on the nature of the binder matrix. Polyaspartic acid-based materials are an attractive binder matrix for LEP coatings. Typically used as a two-component system, it consists of a binder component and a curing agent component. Therefore, the selection of the binder and curing agent combination is a critical step in the development of LEP coatings. The options / selections are based on tensile properties, molecular structure (chemical structure, number of functional groups, molecular weight, etc.) and physical properties (solubility, T g , viscosity, etc.).

[0005] Therefore, obtaining the proper combination of binder(s) and curing agent(s) that can achieve high tensile values ​​for polyaspartic LEP systems is very important, but not a simple task for many of the available combinations.

[0006] Therefore, it is an object of the present invention to provide a wind turbine blade coated with a coating composition having improved tensile properties and durability. Ideally, the coating composition should maintain its properties after exposure to ultraviolet light, be easy to apply, have an acceptable pot life, and dry quickly. It is also desirable that the coating has good adhesion to the underlying coating and / or substrate and few film defects. The inventors have surprisingly found that a wind turbine blade coated with a coating composition comprising a combination of at least one polyaspartic and at least one aliphatic polyisocyanate prepolymer provides an attractive solution. In particular, the inventors have found that such a coating composition further comprising an alicyclic diamine aldimine has attractive properties. Summary of the invention

[0007] Thus, in a first aspect, the present invention provides a wind turbine blade, preferably a leading edge of a wind turbine blade, coated with a coating composition comprising:

[0008] (A) at least one polyaspartic acid (polyaspartic acid) selected from the group consisting of polyaspartic acid esters, polyether aspartic acid esters, and mixtures thereof; and

[0009] (B) at least one aliphatic polyisocyanate prepolymer curing agent;

[0010] Wherein component (A) further comprises an alicyclic diamine aldimine.

[0011] In other aspects, the present invention provides a wind turbine blade, preferably a leading edge of a wind turbine blade, coated with a coating composition comprising:

[0012] (A) at least one polyaspartic acid selected from the group consisting of polyaspartic acid esters, polyether aspartic acid esters, and mixtures thereof; and

[0013] (B) at least one aliphatic polyisocyanate prepolymer curing agent;

[0014] wherein component (A) further comprises an alicyclic diamine aldimine, and component (B) further comprises an aliphatic polyisocyanate different from the at least one aliphatic polyisocyanate prepolymer curing agent.

[0015] In another aspect, the present invention provides the use of a coating composition as defined above for coating at least a portion of a wind turbine blade, preferably the leading edge of a wind turbine blade.

[0016] definition

[0017] Leading edge protection (LEP) coatings are used herein to refer to coatings applied to protect the highest speed (usually greater than 300 km hr) -1 ) is a coating on the outer peripheral part (leading edge) of the blade. Primer, intermediate coating, topcoat and transition coating (tiecoat) are all terms well known in the art.

[0018] When we quote the "molecular weight" of a particular component, we are referring to the theoretical value of the molecular weight of an ideal molecule. It is usually used for small molecules.

[0019] When referring to the "number average molecular weight (M)" of a particular component (usually a polymer component), n )”, we mean the total weight divided by the total number of molecules. n is a value obtained by analysis, for example, by end group analysis or GPC.

[0020] In the context of the present invention, "curing" refers to the process of obtaining a solid layer of a coating system from a liquid component. Curing can be carried out, for example, by a chemical reaction and / or by evaporation of a solvent. It should be understood that the curing reaction may not always be complete, for example, after "curing" occurs, unreacted functional groups, such as isocyanate groups, may remain. Therefore, with respect to "curing", "cured" or "allowing to cure", we cover both partial curing and complete curing.

[0021] In the context of the present invention, "coated" means at least partially coated. Thus, the coating composition may coat part or all of a wind turbine blade. DETAILED DESCRIPTION

[0022] The present invention relates to a wind turbine blade coated with a coating composition comprising at least one polyaspartic component (A) and at least one aliphatic polyisocyanate prepolymer component (B). In addition, the coating composition comprises an alicyclic diamine aldimine in component (A).

[0023] Component (A)

[0024] Component (A) comprises at least one polyaspartic acid material selected from the group consisting of polyaspartic acid esters, polyether aspartic acid esters and mixtures thereof.

[0025] In one embodiment, component (A) contains only one polyaspartic acid. Therefore, in this embodiment, the polyaspartic acid consists of polyaspartic acid ester or polyether aspartic acid ester, preferably polyaspartamide.

[0026] In an alternative embodiment, component (A) comprises a mixture of at least one polyaspartic acid ester and at least one polyether aspartic acid ester. In this embodiment, the weight ratio of at least one polyaspartic acid ester to at least one polyether aspartic acid ester is preferably in the range of 99:1 to 1:99, more preferably 80:20 to 20:80, 75:25 to 25:75, even more preferably 50:50.

[0027] Any suitable polyaspartate may be used, however typically the polyaspartate is a polyaspartate comprising a sterically hindered secondary amine and an ester group. Suitable polyaspartates are described, for example, in WO2016049104A1.

[0028] The polyaspartic acid ester may include one or more polyaspartic acid esters corresponding to formula (I):

[0029]

[0030] wherein: n is an integer from 2 to 6; Z represents an aliphatic residue; and R 1 and R 2 represents an organic group which is inert toward isocyanate groups under the reaction conditions and may be the same or different organic groups.

[0031] In formula (I), the aliphatic residue Z may correspond to a linear or branched alkyl and / or cycloalkyl residue of an n-valent polyamine (polyamine), which reacts with a dialkyl maleate in a Michael addition reaction to give a polyaspartate.

[0032] For example, the residue Z may correspond to an aliphatic residue of an n-valent polyamine, including, but not limited to, ethylenediamine; 1,2-diaminopropane; 1,4-diaminobutane; 1,6-diaminohexane; 2,5-diamino-2,5-dimethylhexane; 2,2,4- and / or 2,4,4-trimethyl-, 6-diaminohexane; 1,11-diaminoundecane; 1,12-diaminododecane; 1-amino-3,3,5-trimethyl-5-amino-methylcyclohexane; 2,4'- and / or 4,4'-diaminodicyclohexylmethane; 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane; 2,4,4'-triamino-5-methyldicyclohexylmethane; a primary amino group having an aliphatic bond and M n 148 g mol -1 Up to 6000 g mol -1 polyether polyamine; any isomers thereof and any combination thereof.

[0033] In certain embodiments, the residue Z can be derived from 1,4-diaminobutane; 1,6-diaminohexane; 2,2,4- and / or 2,4,4-trimethyl-1,6-diaminohexane; 1-amino-3,3,5-trimethyl-5-aminomethylcyclohexane; 4,4'-diaminodicyclohexylmethane; 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane; or 1,5-diamino-2-methyl-pentane.

[0034] In certain embodiments, the polyaspartic acid ester comprises one or more compounds corresponding to formula (I), wherein n is an integer from 2 to 6, in some embodiments n is an integer from 2 to 4, and in some embodiments n is 2.

[0035] Examples of commercially available polyaspartic acid esters are Desmophen NH1220, NH1420, NH1422, NH1423, NH1520, NH1521, NH1423 LF, and NH1523 LF, all from Covestro, and F220, F221, F420, F421, F520, all from Feiyang, and IC20 and IC40 from Evonik.

[0036] Any suitable polyether aspartate may be used, however typically the polyether aspartate is one having the following formula (II):

[0037]

[0038] Each R represents a straight or branched C1-C 10 An alkyl residue, such as a linear or branched C1-C6 alkyl residue, such as a methyl, ethyl, propyl or butyl residue; and wherein X is a polyether.

[0039] In one embodiment, the present invention is directed to a coating composition comprising a blend of polyether aspartates, wherein X is a polyether having a repeating unit of the structure:

[0040]

[0041] Wherein m is in the range of 2 to 35.

[0042] The blend of polyether aspartates may comprise at least two different polyether aspartates having different numbers of repeating units in X. In one embodiment, the blend is such that the average value of m is in the range of 2 to 10, such as 2 to 6, such as 2 to 4, such as 2.5 to 3.

[0043] Polyether aspartic acid esters can be prepared by reacting one or more polyether polyamines with dialkyl maleates, such as linear or branched C1-C 10Dialkyl maleates, such as linear or branched C1-C6 dialkyl maleates, such as diethyl maleate. For example, the polyether aspartate can be prepared by using an amount of reactants such that there is at least one equivalent, and in some embodiments about one equivalent, of olefinic double bonds per equivalent of primary amino groups. Examples of methods for preparing polyether aspartates can be found in WO 2014 / 151307 and Chen et al., RSC Advances (2018), 8:13474-13481.

[0044] Suitable polyether polyamines that can be reacted with the dialkyl maleate in a Michael addition reaction to prepare the polyether aspartic acid esters used in the coating composition of the present invention include Jeffamine polyetheramines commercially available from Fluntsman Corporation, The Woodlands, Tex.; for example, polyetheramines from the Jeffamine D series, such as Jeffamine D-230.

[0045] In one embodiment, the blend of polyether polyamines comprises a blend of polyether polyamines according to the following formula (III),

[0046]

[0047] wherein p is a number having an average value of at least 2, such as from 2 to 35, or from 2 to 8, or from 2.5 to 6.1, wherein the blend comprises: (1) from about 50 wt % to 99 wt %, such as from 50 wt % to 90 wt %, or in some cases from 80 wt % to 90 wt % of a polyether polyamine according to the formula, wherein p has an average value of 2.5; and (2) from about 1 wt % to 50 wt %, such as from 10 wt % to 50 wt %, or in some cases from 10 wt % to 20 wt % of a polyether polyamine according to the formula, wherein p has an average value of 6.1.

[0048] Examples of blends of polyether aspartic acid esters suitable for use in the present invention are Desmophen NH 1720 (formerly known as Desmophen NH 2850XP) and Desmophen NH 1723LF from Covestro, both of which have an equivalent weight of about 290-295 g mol -1 , the viscosity at 25°C is ≥80mPa·s, and the amine value is between 170-210mg KOH / g.

[0049] Component (A) further comprises a cycloaliphatic diamine aldimine, preferably isophorone diamine aldimine, such as Vestamin A139 from Evonik. Suitable aldimines include, but are not limited to, 1,3,3-trimethyl-N-(2-methylpropylidene)-5-[(2-methylpropylidene)amino]cyclohexanemethylamine. Aldimines include the group RCH=NR or RCH=NH, i.e., are formed by condensation of an aldehyde with a primary or secondary amine. Preferably, the structure of the aldimine is RCH=NR.

[0050] The alicyclic diamine aldimine of the present invention preferably comprises a 5-membered or 6-membered aliphatic carbon ring, which may be substituted by an alkyl group, such as a C1-4 alkyl group.

[0051] The N atom of the imine may be bound to the carbocyclic ring or may be separated from the ring by a further alkylene chain. It is preferred if the alicyclic diamine aldimine contains two nitrogen atoms. It is preferred if the aldimine of the invention contains at least two aldimine groups, such as two aldimine groups. It is preferred that the aldimine of the invention contains only C, H and N atoms. In one embodiment, the molecular weight of the aldimine is less than 400 g mol -1 .

[0052] Any suitable alicyclic diamine aldimine may be used, including those prepared from an aldehyde and a polyamine containing two or more, preferably 2 to 6, and more preferably 2 to 4 primary amino groups. The polyamines include those prepared from an aldehyde and a polyamine containing two or more, preferably 2 to 6, and more preferably 2 to 4 primary amino groups. -1 High molecular weight amines having a molecular weight of 400 to about 10,000, preferably 800 to about 6,000, and low molecular weight amines having a molecular weight below 400. Examples of these polyamines are those in which the amino groups are attached to aliphatic or preferably alicyclic carbon atoms.

[0053] Suitable low molecular weight polyamine starting compounds include tetramethylenediamine, ethylenediamine, 1,2- and 1,3-propylenediamine, 2-methyl-1,2-propylenediamine, 2,2-dimethyl-1,3-propylenediamine, 1,3- and 1,4-butylenediamine, 1,3- and 1,5-pentanediamine, 2-methyl-1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, , 1,11-dodecanediamine, 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, 4,4'-, 2,4'- and 2,2'-diaminodicyclohexylmethane, bis(4-amino-3-methylcyclohexyl)-methane, 1,2- and / or 1,4-cyclohexanediamine, 1,3-bis(methylamino)-cyclohexane, 1,8-p-menthanediamine, hydrazine, hydrazides of semi-carbazidocarboxylic acids, bis-hydrazides, bis-semicarbazides, N,N,N-tri(2-aminoethyl)amine, guanidine, N-(2-aminoethyl)-1,3-propylenediamine, polyoxypropyleneamine, polyoxyethyleneamine, and mixtures thereof.

[0054] Preferred polyamines are 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane (isophoronediamine or IPDA), 4,4′-, 2,4′- and 2,2′-diaminodicyclohexylmethane, bis(4-amino-3-methylcyclohexyl)methane, 1,6-diaminohexane, 2-methylpentamethylenediamine and ethylenediamine, 4,4′-diaminodicyclohexylmethane, optionally in a mixture with its isomers.

[0055] Suitable high molecular weight polyamines correspond to the polyols defined below, which are used to prepare the NCO prepolymers, but differ in that the terminal hydroxyl groups are converted to amino groups by amination or by reaction of the hydroxyl groups with diisocyanates and subsequent hydrolysis of the terminal isocyanate groups to amino groups. Preferred high molecular weight polyamines are amine-terminated polyethers, such as the Jeffamine resins available from Texaco.

[0056] Suitable aldehydes are those corresponding to the formula

[0057] O=CHCH(R1)(R2)

[0058] wherein R1 and R2 may be the same or different and represent an aliphatic hydrocarbon group, preferably containing 1 to 10, more preferably 1 to 6 carbon atoms, or R1 and R2 together with the β-carbon atom form an alicyclic ring. At least one of the aldehyde or polyamine reactants comprises an alicyclic ring.

[0059] Examples of suitable aldehydes include isobutyraldehyde, 2-ethylhexanal, 2-methylbutyraldehyde, 2-ethylbutyraldehyde, 2-methylvaleraldehyde, 2,3-dimethylvaleraldehyde, 2-methylundecanal, and cyclohexane carboxyaldehyde.

[0060] Aldimines can be prepared in a known manner by reacting polyamines with aldehydes in stoichiometric amounts or with excess aldehydes. Excess aldehydes and the resulting water can be removed by distillation. The reaction can also be carried out in solvents other than ketones. After the reaction is complete, the solvent can also be removed by distillation.

[0061] A particularly preferred aldimine is isophoronediamine aldimine, for example Vestamin A-139 from Evonik.

[0062] It should be understood that in the presence of moisture, aldimines are unstable and can be stored as a third component to maintain functionality. In order to maintain aldimine functionality, dehumidifiers such as molecular sieves, oxazolidines, p-toluenesulfonyl isocyanate, etc. can also be used. Relative to the combined total weight of at least one polyaspartic acid substance and aldimine, the alicyclic diamine aldimine can be present in an amount of 3wt% to 30wt%, preferably 10wt% to 20wt%. Component (A) can include 30wt% to 80wt% of a polyaspartic acid component, such as 40wt% to 70wt%. Component (A) can include 2.0wt% to 15wt% of an aldimine component, such as 3.0wt% to 12wt%.

[0063] Any individual additional component, such as pigment, filler, etc., may form up to 35 wt% of component (A), such as up to 30 wt% of component (A). The total amount of additional components in component (A), i.e. those components other than the polyaspartic acid and aldimine components, may be 75 wt% or less, such as 50 wt% or less.

[0064] It should be appreciated that component (A) may also include other resins / binders known in the art to form chemical bonds with isocyanates. These include, but are not limited to, polyethers, polyesters, polycarbonates, polyamines and polyols of polyvinyls and polyacrylics. As other binders, polycarbonate polyols are particularly preferred. Such binders are well known in the art and are commercially available.

[0065] Component (B)

[0066] Component (B) comprises at least one aliphatic polyisocyanate prepolymer curing agent. In this context, "aliphatic" means that the prepolymer is aliphatic throughout its structure, i.e. both the backbone and the end groups are aliphatic. Suitable polyisocyanate prepolymers are well known in the art.

[0067] The polyisocyanate prepolymers used in the present invention are most commonly made by reacting (urethanizing) an excess of diisocyanate with long-chain, usually difunctional, polyols, particularly polyether, polyester and polycarbonate polyols, and removing the excess monomeric diisocyanate.

[0068] Thus, the polyisocyanate prepolymer may contain urethane linkages and typically has an isocyanate functionality of about 2.

[0069] They can also be made by reacting thiol or amine functional compounds with diisocyanates. In the latter case, polyureas are formed.

[0070] The end result is to obtain a compound having an isocyanate functional group instead of a hydroxyl group at the end. Therefore, the polyisocyanate prepolymer preferably contains one or more carbamate and / or urea (excluding the carbamoyl urea of ​​biuret) bonds. In particular, the polyisocyanate prepolymer preferably contains one or more carbamate bonds.

[0071] The polyisocyanate prepolymers most relevant in the present context have a functionality of about 2 and contain urethane or urea bonds. It is preferred if the polyisocyanate prepolymers are neither allophanates nor uretdiones.

[0072] The aliphatic polyisocyanates of the present invention preferably contain at least 3 isocyanate groups, ie have a functionality of three or more. For polyisocyanate prepolymers, the functionality is usually less than 3, for example up to 2.5, and usually about 2.

[0073] Examples of suitable aliphatic monomeric polyisocyanates include hexamethylene diisocyanate (HDI), 2,2,4- and / or 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, dodecanedimethylene diisocyanate, 1,4-diisocyanatocyclohexane, 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (IPDI), 1,5-pentamethylene diisocyanate (PDI), and 2,4′- and / or 4,4′-diisocyanato-dicyclohexylmethane (HDI). 12 MDI).

[0074] Commercially available examples of these monomeric polyisocyanates include:

[0075] Desmodur H, ex Covestro, monomeric aliphatic diisocyanate, HDI, equivalent weight 84, functionality 2.

[0076] Desmodur I, ex Covestro, monomeric aliphatic diisocyanate, IPDI, equivalent weight 111, functionality 2.

[0077] Desmodur W, ex Covestro, monomeric aliphatic diisocyanate, H12MDI, equivalent weight 131, functionality 2.

[0078] Desmodur ECO N 7300, aliphatic polyisocyanate, PDI trimer, 21.5% NCO (by weight based on supplied form), functionality 3.7.

[0079] The prepolymer can be made from a molecular weight of 62 g mol -1 to 299 g mol -1 Examples include ethylene glycol, propylene glycol, trimethylolpropane, 1,6-dihydroxyhexane; low molecular weight hydroxyl-containing esters of these polyols with dicarboxylic acids of the types listed below; low molecular weight ethoxylation and / or propoxylation products of these polyols; and mixtures of the above-mentioned multivalent modified or unmodified alcohols.

[0080] Preferably, the prepolymer is composed of a relatively high molecular weight (e.g., greater than 299 g mol -1 Each molecule of these polyhydroxy compounds has at least two hydroxyl groups, and more preferably has a hydroxyl content of 0.5-17 wt%, preferably 1-10 wt%.

[0081] The polyisocyanate prepolymers generally have an isocyanate content of 0.5 to 30% by weight, preferably 1 to 20% by weight, and are prepared in a known manner by reacting the required starting materials at an isocyanate (NCO) / hydroxyl (OH) equivalent ratio of 1.05:1 to 10:1, preferably 1.1:1 to 3:1, which reaction is optionally followed by distillative removal of any unreacted volatile starting polyisocyanate still present. Particularly preferred prepolymers are IPDI prepolymers and HDI prepolymers.

[0082] In one embodiment, the preferred polyisocyanate prepolymer of the present invention has an NCO content (in wt%) lower than that of the aliphatic polyisocyanate. The polyisocyanate prepolymer of the present invention may have an NCO content of 11 wt% or less. The aliphatic polyisocyanate used in the present invention may have an NCO content of 11.5 wt% or more.

[0083] Preferably, the prepolymer has an isocyanate functionality of from 1.2 to 3.5, preferably from 1.5 to 3.0, more preferably from 1.8 to 2.2, for example 2.

[0084] Commercially available isocyanate prepolymers from Covestro:

[0085] Desmodur E 40480 MPA, aliphatic IPDI prepolymer (formerly known as Desmodur XP2406) (2.4-3.2% NCO by weight based on supplied form), functionality 2.

[0086] Desmodur E2863 XP, aliphatic HDI prepolymer (about 11% NCO by weight based on supplied form), functionality 2.2.

[0087] Desmodur XP 2599, aliphatic HDI prepolymer (5.5-6.5% NCO by weight based on the supplied form).

[0088] ANDUR AL80-5AP, aliphatic polyether from Anderson Development Company, polytetramethylene ether glycol (PTMEG), and H 12 MDI (3.8-4.2% NCO by weight based on supplied form).

[0089] Prepolymers from Lanxess:

[0090] LFH E520 HDI polyether, 5.00-5.40% NCO (by weight based on supplied form).

[0091] LFH E710 HDI polyether, 6.80-7.40% NCO (by weight based on supplied form), functionality 2.

[0092] LFH C840 HDI polycaprolactone, 8.20-8.60% NCO (by weight based on supplied form).

[0093] LFH R600 HDI polycarbonate, 5.60-6.40% NCO (by weight based on supplied form).

[0094] LW 520H 12 MDI polyether, 4.60-4.90% NCO (by weight based on supplied form).

[0095] LW 570H 12 MDI polyether, 7.35-7.65% NCO (by weight based on supplied form).

[0096] SC 7902 IPDI polyether, 3.90-4.10% NCO (by weight based on supplied form).

[0097] SC 7930 HDI Biuret castor oil, 9.00-12.00% NCO (by weight based on supplied form).

[0098] SC 7931 IPDI polyether, 2.70-3.20% NCO (by weight based on supplied form), functionality 2.

[0099] DP9A / 997 IPDI polyether, 3.50-4.00% NCO (by weight based on supplied form).

[0100] Component (B) may further comprise an aliphatic polyisocyanate different from the at least one aliphatic isocyanate prepolymer curing agent. Suitable aliphatic polyisocyanates are well known in the art. The aliphatic polyisocyanate preferably does not contain any urethane bonds. The aliphatic polyisocyanate preferably does not contain any urea bonds.

[0101] In the preferred coating composition of the present invention, the aliphatic polyisocyanate is a derivative of the above-mentioned monomeric polyisocyanate, which is conventional in the art. These derivatives include polyisocyanates containing biuret groups. Examples of particularly preferred derivatives include mixtures of N, N', N"-tris(6-isocyanatohexyl)-biuret and its higher homologues (higher homologues), and N, N', N"-tris(6-isocyanatohexyl)-isocyanurate and its higher homologues containing more than one isocyanurate ring.

[0102] In a particularly preferred embodiment, the aliphatic polyisocyanate is an isocyanate biuret or an isocyanate trimer, most preferably an isocyanate trimer.

[0103] Examples of suitable commercially available polyisocyanates are:

[0104] From Covestro:

[0105] Desmodur N3900 (formerly known as VP2410, aliphatic polyisocyanate, aliphatic polyisocyanate, based on HDI, 23.5% NCO (based on the supplied form by weight), functionality 3.2.

[0106] Desmodur N3600, aliphatic polyisocyanate, HDI trimer, 23% NCO (by weight based on supplied form), functionality 3.2.

[0107] Desmodur N3800, aliphatic polyisocyanate, HDI trimer, 11% NCO (by weight based on supplied form), functionality 3.8.

[0108] Desmodur N3300, aliphatic polyisocyanate, HDI trimer, 23% NCO (by weight based on supplied form), functionality 3.5.

[0109] Desmodur N3390, aliphatic polyisocyanate, HDI trimer, 19.6% NCO (by weight based on supplied form), functionality 3.5.

[0110] Desmodur N100, aliphatic polyisocyanate, HDI biuret, 22% NCO (by weight based on supplied form), functionality 3.8.

[0111] Desmodur N 3200, aliphatic polyisocyanate, HDI biuret, 23% NCO (by weight based on the supplied form), functionality 3.5.

[0112] Desmodur N75 BA, MPA or MPA / X, aliphatic polyisocyanate, HDI biuret, 16.5% NCO (by weight based on supplied form), functionality 3.8.

[0113] Bayhydur VP LS2319, aliphatic polyisocyanate.

[0114] Desmodur Z 4470BA, aliphatic polyisocyanate, IPDI trimer, 11.9% NCO (by weight based on supplied form), functionality 3.5.

[0115] Desmodur NZ 300, aliphatic polyisocyanate, blend of HDI and IPDI.

[0116] From Vencorex:

[0117] Tolonate HDT-LV2, ex.Vencorex), aliphatic polyisocyanate.

[0118] Tolonate HDT90, aliphatic polyisocyanate

[0119] Tolonate IDT 70B, aliphatic polyisocyanate, IPDI trimer / homopolymer, 11.3-13.3% NCO (by weight based on supplied form).

[0120] From BASF:

[0121] Basonat HI 190B / S, aliphatic polyisocyanate.

[0122] Basonat HB 175MP / X, aliphatic polyisocyanate HDI biuret, 16-17% NCO (by weight based on the supplied form).

[0123] Basonat HB 100, aliphatic polyisocyanate HDI biuret, 22-23% NCO (by weight based on the supplied form).

[0124] Basonat HB 275B, aliphatic polyisocyanate HDI biuret, 16-17% NCO (by weight based on the supplied form).

[0125] If present, an aliphatic polyisocyanate different from the aliphatic isocyanate prepolymer curing agent is preferably present in an amount less than the aliphatic polyisocyanate prepolymer curing agent. For example, the aliphatic polyisocyanate may be present in an amount of 2.5 wt % to 30 wt %, such as 5 wt % to 15 wt %, relative to the combined total weight of the at least one aliphatic polyisocyanate prepolymer curing agent and the aliphatic polyisocyanate.

[0126] Component (B) may include 70 wt% or more of an aliphatic polyisocyanate prepolymer curing agent. In some embodiments, component (B) consists of an aliphatic polyisocyanate prepolymer curing agent. Component (B) may also include 2.5 wt% to 30 wt%, such as 5.0 wt% to 15 wt% of at least one aliphatic polyisocyanate.

[0127] Other components

[0128] The coating composition of the present invention may also include other substances commonly used in coating formulations, such as fillers (extenders), pigments, matting agents, solvents and additives, such as waxes, dyes, dispersants, wetting agents, defoamers, surfactants, adhesion promoters, light stabilizers (e.g., hindered amine light stabilizers (HALS) and / or (one or more) UV absorbers), water scavengers and thixotropic agents.

[0129] In a preferred embodiment, the coating composition comprises a UV stabilizer and / or a UV absorber. Particularly preferred UV stabilizers are HALS, such as bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and Tinuvin 292 from BASF, which is a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate methyl ester.

[0130] In a specific embodiment, the coating composition comprises an adhesion promoter. Examples of suitable adhesion promoters include alkoxysilanes, such as those known under the trade name Dynasylan from Evonik, for example Dynasylan AMEO and Dynasylan 1189, and Silquest from Momentive, such as A1524 (similar to Evonik's VPS2101, 3-ureidopropyltrimethoxysilane), and NCO alkoxysilane hybrids, such as Silquest from Covestro. 2873.

[0131] The total amount of additives will generally comprise up to about 25 wt%, for example up to 20 wt%, desirably up to 15 wt%, based on the total weight of the entire coating composition. The additives may comprise only 1 wt% or less of the composition.

[0132] Examples of fillers are minerals such as dolomite, plastorite, calcite, quartz, barite, magnesite, silica, nepheline syenite, wollastonite, talc, chlorite, mica, kaolin, pyrophyllite and feldspar; synthetic inorganic compounds such as calcium carbonate, magnesium carbonate, barium sulfate, calcium silicate and silica; polymers and inorganic microspheres such as uncoated or coated hollow and solid glass beads, uncoated or coated hollow and solid ceramic beads, porous and dense beads of polymeric materials such as poly(methyl methacrylate), poly(methyl methacrylate-co-ethylene glycol dimethacrylate), poly(styrene-co-ethylene glycol dimethacrylate), poly(styrene-co-divinylbenzene), polystyrene, polyvinyl chloride. Pigments of interest include organic pigments and inorganic pigments such as titanium dioxide.

[0133] Preferred examples of suitable solvents are organic solvents such as toluene, xylene and naphtha solvents; ketones such as methyl ethyl ketone, methyl isobutyl ketone, diacetone alcohol and cyclohexanone; esters such as methoxypropyl acetate, n-butyl acetate and 2-ethoxyethyl acetate; and mixtures thereof. Particularly preferred solvents are esters such as n-butyl acetate, tert-butyl acetate, 1-methoxy-2-propyl acetate, and most preferably n-butyl acetate and / or 1-methoxy-2-propyl acetate.

[0134] The solvent preferably forms less than 20wt% of the coating composition. It should be understood that the weight percentage range of the solvent is relative to the coating composition before curing (i.e., before the coating is cured and dried). Relative to the gross weight of the coating composition, any pigment preferably accounts for 10wt% to 30wt%, such as 15wt% to 25wt%. Relative to the gross weight of the coating composition, the filler usually preferably accounts for 0wt% to 40wt%, such as 2.5wt% to 30wt%, such as 5wt% to 20wt%.

[0135] Any additional components may be considered part of component (A).

[0136] Coating composition

[0137] In a preferred embodiment, the coating composition of the present invention can be cured at ambient temperature, preferably at room temperature, i.e. when the components are mixed, the coating composition will cure at the temperature in the environment under consideration without applying heat. This can generally be in the range of 5°C to 50°C. Preferably, curing occurs at 10°C to 35°C, more preferably at room temperature, i.e. in the range of 15°C to 30°C. It should be understood that since the coating compositions of the present invention are curable, they can be referred to as curable coating compositions.

[0138] The coating composition is preferably composed of several parts (e.g., two or more parts) to prevent premature curing and is therefore shipped as a kit of parts. Before use, the components should be combined and thoroughly mixed. Conventional mixing techniques can be used.

[0139] In one embodiment, the coating composition of the present invention can be supplied as a 3-component multi-part kit to maximize the storage stability of the coating composition. The inventors have found that if the coating composition is supplied as a two-component kit with the curing agent and the polyaspartic acid in separate containers, the storage stability may be compromised. Therefore, it is preferred if the aldimine is added just before applying the coating composition (A) to the substrate. This prevents the aldimine from reacting or deactivating prematurely.

[0140] Therefore, the polyaspartic acid component (A), the aldimine component and the curing agent component are preferably supplied in separate containers in order to be mixed shortly before application to the wind turbine blade.

[0141] Thus, viewed from another aspect, the invention provides a kit of parts suitable for use in producing a coating composition of the invention comprising:

[0142] A first container comprising at least one polyaspartic acid material selected from the group consisting of polyaspartic acid esters, polyether aspartic acid esters, and mixtures thereof;

[0143] a second container comprising at least one aliphatic polyisocyanate prepolymer curing agent;

[0144] The third container contains alicyclic diamine aldimine.

[0145] It should be understood that in order to ensure storage stability, the first container contains no curing agent and no aldimine, the second container contains no polyaspartic acid and no aldimine, and the third container contains no polyaspartic acid and no curing agent.

[0146] If a two-component system is used, the use of a water scavenger, such as those discussed above, can improve the storage stability of the aldimine component.

[0147] The polyaspartic component (A) (i.e., at least one polyaspartic material plus aldimine) and the polyisocyanate component (B) (i.e., at least one aliphatic polyisocyanate prepolymer plus optional aliphatic polyisocyanate) are generally present in an amount corresponding to a ratio of NCO group equivalents to the total number of amine (NH) groups of 0.75-1.25:1, more preferably 0.9-1.1:1.

[0148] The weight ratio of the total formulation of component (A) to the total formulation of component (B) (i.e. each of component (A) and component (B) including additives and solvents) is generally in the range of 1:5 to 5:1, preferably 1:3 to 3:1, such as 1:2 to 2:1, for example 1:1.

[0149] In a preferred embodiment, the coating composition has an initial gloss at 60° after curing (ie before exposure) of greater than 10 gloss units, preferably greater than 20 gloss units, more preferably greater than 30 gloss units.

[0150] As described under "Test Methods", the coating composition after curing preferably has a tensile strain of greater than 200%, more preferably greater than 250%, such as greater than 300%, when measured at 23°C using a modified procedure based on ISO 527.

[0151] The coating composition preferably has a tensile stress after curing of greater than 20 MPa, more preferably greater than 25 MPa, such as greater than 30 MPa, when measured at 23°C using a modified procedure based on ISO 527 as described under "Test Methods".

[0152] The coating composition of the present invention preferably has a solid content of 75 wt% or more, such as 80 wt% or more, for example 85 wt% or more, relative to the total weight of the coating composition.

[0153] The coating compositions of the present invention, after curing, desirably have a gloss retention greater than 50% as measured after 2000 hours QUV-A exposure at 60° according to ISO 16474-3, test cycle 1.

[0154] The coating compositions of the present invention, after curing, desirably have a gloss retention of greater than 30% as measured according to ISO 11507 Method A at 60° after 2000 hours QUV-B exposure.

[0155] Coating Systems and Application

[0156] The coating composition of the present invention is used to coat a wind turbine blade, preferably the leading edge of a wind turbine blade. Typical turbine blades are composed of a material comprising a synthetic resin composite material comprising an epoxy resin, a vinyl ester resin, a polyurethane, a glass or carbon fiber reinforced resin. In a particularly preferred embodiment, the substrate is the leading edge of a wind turbine blade.

[0157] Hence, the present invention relates to a wind turbine blade at least partially coated with a coating composition as defined above. The present invention also relates to the use of a coating composition as defined above for coating at least a portion of a wind turbine blade, preferably the leading edge of a wind turbine blade.

[0158] The coating composition may be applied by any conventional method, such as brushing, rolling or spraying (airless or conventional). Preferably, conventional spraying is used.

[0159] The layer formed using the coating composition of the present invention preferably has a dry film thickness of 50 μm to 500 μm, more preferably 100 μm to 500 μm, such as 150 μm to 500 μm. It should be understood that any layer can be laid using a single or multiple coatings (applications). Preferably, 2 to 6 layers are applied, more preferably 2 to 4 layers.

[0160] The coating composition is usually applied as part of a coating system with more than one layer. In such a system, the coating composition of the present invention is preferably, but not necessarily, applied as the outermost layer. The composition of the present invention can be applied to any pretreatment layer suitable for polyaspartic acid coating.

[0161] Typically, the time interval between applying each layer is less than 24 hours, preferably in the range of 1 to 24 hours, more preferably 1 to 12 hours, such as 1 to 6 hours at 23°C and 50% relative humidity.

[0162] In the context of the present invention, the term "tiecoat" refers to a coating layer that acts as a bridge between, for example, a substrate, a primer or basecoat or a filler and a coating. Therefore, it is understood that when we refer to a "substrate" or a "substrate surface", we mean the substrate itself or any pretreatment layer that has been applied to at least a portion of the substrate. Thus, the coating composition of the present invention can be applied directly to at least a portion of the substrate or to any pretreatment layer designed for a polyurethane or polyurea topcoat (topcoat) based on a polyol, polyamine, polyaspartate or polyetheraspartate.

[0163] In a preferred embodiment, the coating composition of the present invention is applied as part of the following coating system: an optional filler layer (also commonly referred to as putty, such as a polyurethane with a high filler content), a primer layer (e.g., polyurethane or polyurea), a transition coating and a LEP coating, in this order, wherein the coating composition of the present invention forms the LEP coating. Sometimes the LEP coating can be coated with another coating, but most commonly the LEP coating is the outermost coating in the coating system. Preferably, the primer is a water-based, solvent-based or solvent-free polyurethane or polyaspartic coating. Preferably, the filler is a polyurethane coating with a high solid content, preferably 80-100 wt% solids, typically greater than 97 wt% solids.

[0164] The layers formed using the coating system of the present invention preferably have the following dry film thicknesses: filler (0-2000 μm, applied on 0-3 coats), primer (60-150 μm, applied on 1-2 coats), transition coating (20-50 μm, applied on 1 coat), LEP coating (150-500 μm, applied on 2-6 coats). It should be understood that any layer can be laid down using a single or multiple application of the coating (paint), depending on the coating method and the area of ​​use.

[0165] The invention will now be described with reference to the following non-limiting examples.

[0166] Example

[0167] General procedure for preparing compositions

[0168] The two components of the various coating compositions were prepared by combining the respective ingredients in a manner known to the person skilled in the art and mixing them uniformly in a dissolver. For each coating composition, the two components were uniformly mixed in the proportions shown in Table 1, wherein the coating compositions are indicated by I = according to the invention and C = comparative example.

[0169] Test Method

[0170] Tensile Testing - Stress and Strain

[0171] Stress and strain were determined using a modified procedure based on ISO 527. After drying for 2 weeks at 23°C and 50% RH, the paint was applied on a Dupont Mylar film to obtain coating samples with a dry film thickness of 200-250 μm. Samples with a width of 10 mm and a length of 150 mm were then tested at 23°C in a Testometric universal testing machine at a strain rate of 200 mm / min and a gauge length (gauging length) of 50 mm.

[0172] Solid content

[0173] The solid content in the coating composition is calculated according to ASTM D5201.

[0174] Drying time

[0175] Drying time was evaluated at 120 μm wet film thickness (WFT) using a mechanical linear or circular drying time recorder using the Beck-Koller method at 23°C and 50% RH according to ISO 9117-4:2012. Drying time ratings are as follows:

[0176] F = Fast, i.e. hard dry within 6 hours

[0177] M = Medium, i.e. hard drying within 6-24 hours

[0178] S = Slow, i.e. not hardened within 24 hours

[0179] Artificial Weathering

[0180] Aluminum panels were coated with 300 μm of WFT LEP and dried for 2 weeks at 23 °C and 50% RH before exposure as follows:

[0181] QUV-A, according to ISO 16474-3, according to Test Cycle 1. Test Cycle No. 1: 4 hours of ultraviolet light at 60°C using a UVA-340 lamp (UVA-340, irradiance 0.83 W / m at 340 nm) 2 ), followed by condensation at 50°C for 4 hours, for a total of 1000 to 2000 hours.

[0182] QUV-B, according to ISO 11507 Method A, using UVB-313 nm lamp, according to the following cycle: 4 hours at 60 ° C UV light (irradiance 0.71 w / m 2 ), followed by condensation at 50°C for 4 hours, for a total of 1000 to 2000 hours.

[0183] Gloss was measured at an angle of 60° after 1000 and 2000 hours of exposure according to ISO 2813:2014.

[0184] Rain erosion test

[0185] The rain erosion test was carried out according to standard ASTM G73-10, where an airfoil shape glass fiber reinforced polymer (GRP) panel, with a panel exposed area length of 23 cm for droplet impact, was coated with a system of primer + transition coating + coating composition. The transition coating composition (see below for details) was applied to a GRP specimen coated with 70 μm of DFT Jotatop BC100 (a commercially available two-component polyurethane-based primer from Jotun A / S). The coating was allowed to dry for 2 hours before applying the LEP coating.

[0186] The LEP coating composition was prepared and applied on top of a 30 μm DFT transition coating (tie coat). Typically, curing occurred by storage at 23°C and 50% RH for two weeks. The coating was applied in two layers with a brush (2x150 μm DFT) with 2-3 hours of drying between layers. The total dry film thickness of the cured coating was 300 μm.

[0187] The coated test panels were attached to each of the three rotating arms and tested at 1527 rpm = 160 m / s, 15-35°C, rainfall intensity 30-35 mm / h, and checked every 30 minutes to visually monitor erosion. The time to erode the surface is used to compare the performance of the coating systems to each other. The longer the coating system can withstand erosion, the better.

[0188] Material

[0189]

[0190]

[0191]

[0192] Transition coating (bonding layer)

[0193] Two-component composition:

[0194] Component A: 1 part by weight of a mixture of 31.5 wt% of type 9 bisphenol A diglycidyl ether (BADGE) resin having an epoxy equivalent weight (EEW) of 2500-4000 and a Mn greater than 3500 g / mol, 31.5 wt% of PMA glycol ether and 37 wt% of xylene.

[0195] Component B: 0.257 parts by weight of an aromatic NCO based on toluene diisocyanate (75 wt% solids in ethyl acetate, based on the supplied form, 13.3 wt% NCO) Prior to coating, both components were mixed homogeneously and applied uniformly on the surface.

[0196] Table 1: Coating compositions by weight and results

[0197]

[0198] * The breaking point of the samples in Table 1 gives the values ​​= ultimate stress and strain values.

[0199] Table 2: RET results for GRP samples coated with topcoat, transition coat and LEP.

[0200] System 1 (Comparative Example) System 2 (Comparative Example) System 3 (invention example) LEP coating composition CE1 CE2 IE2 Time before erosion [hours] 1 2 18

[0201] It is clear from Table 1 that the addition of aldimine results in greater stress values, which improves rain erosion resistance. The significant improvement in RET results when aldimine is added can be further observed by looking at the RET results of System 1 (without aldimine) of CE1 and System 3 (with aldimine) of IE2 in Table 2.

Claims

1. A wind turbine blade, preferably a leading edge of the wind turbine blade, coated with a coating composition, the coating composition comprising: (A) at least one polyaspartic acid selected from the group consisting of polyaspartic acid esters, polyether aspartic acid esters, and mixtures thereof; and (B) at least one aliphatic polyisocyanate prepolymer curing agent; The component (A) further comprises an alicyclic diamine aldimine.

2. The wind turbine blade according to claim 1, wherein: Component (B) further comprises an aliphatic polyisocyanate different from the at least one aliphatic polyisocyanate prepolymer curing agent.

3. A wind turbine blade according to any preceding claim, wherein: The polyaspartic acid substance in component (A) is polyaspartic acid ester or polyether aspartic acid ester, preferably polyaspartic acid ester.

4. A wind turbine blade according to any preceding claim, wherein: Component (A) comprises a mixture of at least one polyaspartic acid ester and at least one polyether aspartic acid ester.

5. A wind turbine blade according to any preceding claim, wherein: The weight ratio of the at least one polyaspartic acid ester to the at least one polyether aspartic acid ester is in the range of 99:1 to 1:99, preferably 50:

50.

6. A wind turbine blade according to any preceding claim, wherein: Component (A) further comprises a UV stabilizer and / or a UV absorber, preferably a hindered amine light stabilizer (HALS), such as bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate.

7. A wind turbine blade according to any preceding claim, wherein: The alicyclic diamine aldimine is isophorone diamine aldimine, preferably 1,3,3-trimethyl-N-(2-methylpropylene)-5-[(2-methylpropylene)amino]cyclohexanemethylamine.

8. A wind turbine blade according to any preceding claim, wherein: Component (A) further comprises an alicyclic diamine aldimine in an amount of 3 wt % to 30 wt % relative to the combined total weight of the at least one polyaspartic acid and the aldimine.

9. A wind turbine blade according to any preceding claim, wherein: Component (B) further comprises an aliphatic isocyanate different from the at least one aliphatic polyisocyanate prepolymer curing agent in an amount of 2.5 wt % to 30 wt % relative to the combined total weight of the at least one aliphatic polyisocyanate prepolymer curing agent and the aliphatic polyisocyanate.

10. A wind turbine blade according to any one of claims 2 to 9, wherein: The aliphatic polyisocyanate is an isocyanate trimer or a biuret, preferably a trimer, and more preferably a trimer of 1,4-diisocyanatocyclohexane or 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (IPDI).

11. A wind turbine blade according to any one of claims 2 to 10, wherein: The at least one aliphatic polyisocyanate prepolymer curing agent has a functionality of two.

12. A wind turbine blade according to any preceding claim, wherein: The at least one polyaspartic acid and aldimine and the at least one aliphatic polyisocyanate prepolymer plus an optional aliphatic polyisocyanate are present in an amount corresponding to a ratio of isocyanate (NCO) group equivalents to the total number of NH groups of 0.75-1.25:1, preferably 0.9-1.1:

1.

13. A wind turbine blade according to any preceding claim, wherein: The weight ratio of component (A) to component (B) is in the range of 1:5 to 5:1, preferably 1:3 to 3:1, more preferably 1:2 to 2:1, for example 1:

1.

14. A wind turbine blade according to any preceding claim, wherein: The coating composition after curing has a tensile stress of greater than 20 MPa, preferably greater than 25 MPa, more preferably greater than 30 MPa when measured at 23°C using a modified procedure based on ISO 527 as described under "Test Methods".

15. Use of a coating composition as defined in any preceding claim for coating at least a portion of a wind turbine blade, preferably the leading edge of a wind turbine blade.

16. A kit of parts comprising: a first container comprising at least one polyaspartic acid material selected from the group consisting of polyaspartic acid esters, polyether aspartic acid esters, and mixtures thereof; a second container comprising at least one aliphatic polyisocyanate prepolymer curing agent; A third container comprises an alicyclic diamine aldimine.

Citation Information

Patent Citations

  • Polyaspartic coating compositions

    WO2014151307A1

  • Flexible polyurea sealant compositions

    WO2016049104A1

Cited By

  • Modified asparagus resin and emulsion

    CN120484226A